PEMBELAJARAN KETERAMPILAN MEMBUAT PEWTER PADA ANAK DENGAN HAMBATAN KECERDASAN RINGAN DI SLB NEGERI PANGKAL PINANG - Hesty Raderza, - (2021)
This study aims to describe the implementation of vocational skills learning to make pewter at SLB Negeri Pangkal Pinang, regarding the objective conditions of students, planning, implementation, evaluation, obstacles experienced and the efforts made, to the marketing process of pewter craft products. This type of research is descriptive and uses a qualitative approach. Data collection techniques in this study used observation, interviews, and documentation techniques. The resource persons in this study were one vice principal for curriculum and two vocational teachers. The results of this study indicate that the implementation of vocational skills learning to make pewter consists of: 1) The objective condition of the ability of children with mild intelligence barriers at SLB Negeri Pangkal Pinang can follow the vocational skills of making pewter and there are no obstacles in the motor aspect. 2) Learning planning, namely holding training to make pewter for teachers and students, as well as preparing tools and materials for making pewter crafts. 3) The implementation process of making pewter crafts is carried out by the teacher as an instructor, and students get different tasks according to their abilities. 4) Evaluation is carried out by the teacher by conducting discussions to improve the learning of pewter making skills. 5) Some of the obstacles experienced were in the aspect of students and teachers as instructors. 6) Efforts are made to deal with the obstacles experienced by providing motivation or encouragement to students in the form of certain strategies so that students want to take part in learning, and looking for special teachers from outside who are experts in pewter skills. Keywords: Vocational Skills, Pewter, Children with Intellectual Barriers